Myers' paradox. (11th March 2021) - Priest, Graham
Abstract: This note is an analysis of the paradox given by Myers (2019). It is shown, assuming that the resources available in paraconsistent logic may be applied, how the conclusion of the paradox may be perfectly acceptable, but that the argument is, nonetheless, invalid. This provides a dialethic solution to the paradox.